Ultrastructure of Mauthner Cells in Fish Adapted to Long-Duration Vestibular Stimulation and the Effect of Ethanol - Nadezhda R. Tiras; Georgy V. Zherdev; Dmitry A. Moshkov (Neural Plasticity)
Adaptation or resistance of fish Mauthner cells (M-cells) to long duration (2 h) vestibular stimulation (LDS)was produced by daily brief and gradually increasing vestibular stimulation (training). The LDS resistance was accompanied by an increase in the number of desmosome-like junctions in the afferent axosomatic synapses. F-actin, the main component of desmosome-like contacts, has been suggested to be responsible for the increased resistance of M-cells to LDS. The purpose of the present study was to investigate the capacity of M-cells to adapt to LDS under the influence of ethanol, which alters the content of F-actin in cells. The experiments were carried out in goldfish fry. Vestibular stimulation (training and LDS) was performed in special drums that were rotated in two planes. The training time was increased from 1 min on day 1 to 30 min on day 30. For ethanol exposure, fish were immersed daily in a 2% ethanol solution for 20 min. To assess the level of resistance to LDS, motor activity indicating the functional state of M-cells was evaluated before and after LDS. The results show that exposure to ethanol reduces the resistance to LDS in both untrained and trained fish. Electron microscopic data demonstrated some structural changes in the synaptic endings located on M-cell soma in ethanol-exposed fish. Wrapping of boutons by cytoplasmic out- growths and myelin- like structures was observed. Morphometric analysis revealed that exposure to ethanol without training decreases the number of desmosome-like contacts, probably due to ethanol-induced depolymerization of cytoskeletal actin. Ethanol exposure also partly suppressed the increase in the number of desmosome-like contacts that occurs as a result of training. In ethanol-treated trained fish, however, a concomitant increase in the length of desmosome-like contacts was observed. As training alone leads to the formation of additional desmosome-like contacts of standard length, it is possible that although a sufficient amount of such structures cannot be formed in the M-cells of ethanol-exposed trained fish, the existing contacts can be elongated. Thus, possibly changes of the actin state are involved in the adaptation of M-cells to LDS.